NURSING CARE HYPOVOLEMIA MANAGEMENT CHILDREN WITH DENGUE HEMORRHAGIC FEVER IN RSHD BENGKULU : DENGUE HEMORRHAGIC FEVER - Kurnia, Septiani Tambang; Wulandari, Dwi (STIKes Mandala Waluya Kendari, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus which is classified as an Arthropod-Borne Virus, genus Flavivirus, and family Flaviviridae. DHF is transmitted through mosquito bites from the genus Aedes, especially Aedes aegypti which can attack all age groups. According to data from the World Health Organization, an estimated 500,000 DHF patients require home care each year and most of the sufferers are children, in Indonesia there are 129,435 cases. This study aims to determine the Description of Nursing Care for Hypovolemia Management in Children with Dengue Hemorrhagic Fever with Hypovolemia. Methods: This case study uses a qualitative descriptive research design using a death process approach, providing a systematic, actual and accurate description of Nursing Care for Hypovolemia Management in Children with Dengue Hemorrhagic Fever with Hypovolemia. Results: there was an increase in fluid status with SLKI at level 3 (moderate) in both patients Conclusion: increase in fluid status with SLKI at level 3 (moderate).